Financial Performance Analysis of Hospitals in North Sumatra - Afiezan, Adam; Muda, Iskandar; Keulana Erwin; Muammar Khaddafi (CV Raskha Media Group, 2025)
This study aims to analyze the financial performance of hospitals in North Sumatra by examining key financial indicators, including liquidity, solvency, and profitability ratios. The research employs a quantitative, descriptive approach, using secondary financial data from hospital financial statements over a specific period. The analysis focuses on assessing the hospitals’ ability to manage resources efficiently, meet short-term and long-term obligations, and sustain operational performance. The results indicate that the overall financial performance of hospitals in North Sumatra is relatively stable, although variations exist among institutions. Liquidity ratios generally fall within acceptable levels, suggesting that hospitals can meet short-term liabilities. Solvency ratios indicate a moderate level of financial risk, while profitability ratios show that some hospitals still face challenges in generating optimal financial returns due to high operational costs and reliance on external funding. The study concludes that improving cost efficiency, strengthening financial management practices, and adopting performance-based management strategies are essential to enhance hospital financial sustainability. These findings provide valuable insights for hospital management and policymakers in developing strategies to improve financial performance and ensure the long-term viability of healthcare services in North Sumatra.